Sequence subfamilies of satellite repeats related to rDNA intergenic spacer are differentially amplified on Vicia sativa chromosomes - Macas, Jiri; Navrátilová, Alice; Mészáros, Tibor (Chromosoma, 2003)
We cloned and sequenced the Vicia sativa 25S-18S rDNA intergenic spacer (IGS) and the satellite repeat S12, thought to be related to the spacer sequence. The spacer was shown to contain three types of subrepeats (A, B, and C) with monomers of 173 bp (A), 10 bp (B), and 66 bp (C), separated by unique or partially duplicated sequences. Two spacer variants were detected in V. sativa that differed in length (2990 and 3168 bp) owing to an extra copy of the subrepeat A. The A subrepeats were also shown to be highly homologous to the satellite repeat S12, which is located in large clusters on chromosomes 4, 5, and 6, and is not associated with the rDNA loci. Sequencing of additional S12 clones retrieved from a shotgun genomic library allowed definition of three subfamilies of this repeat based on minor differences in their nucleotide sequences. Two of these subfamilies could be discriminated from the rest of the S12 sequences as well as from the IGS A subrepeats using specific oligonucleotide primers that labeled only a subset of the S12 loci when used in the primed in situ DNA labeling (PRINS) reaction on mitotic chromosomes. These experiments showed that, in spite of the high overall similarity of the IGS A subrepeats and the S12 satellite repeats, there are S12 subfamilies that are divergent from the common consensus and are present at only some of the chromosomes containing the S12 loci. Thus, the subfamilies may have evolved at these loci following the spreading of the A subrepeats from the IGS to genomic regions outside the rDNA clusters.
Keywords: Molecular Sequence Data; genetické komponenty; DNA, Ribosomal Spacer; Sequence Analysis, DNA; fluorescenční mikroskopie; in situ značení DNA s primerem; Microscopy, Fluorescence; Sequence Alignment; genomová knihovna; DNA primery; Chromosomes, Plant; Base Sequence; sekvence nukleotidů; Tandem Repeat Sequences; Gene Components; sekvenční analýza DNA; chromozomy rostlin; molekulární sekvence - údaje; Vicia sativa; Primed In Situ Labeling; DNA Primers; Genomic Library; sekvenční seřazení; tandemové repetitivní sekvence; mezerníky ribozomální DNA